2013
DOI: 10.1261/rna.037606.112
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for RNA–RNA interactions at the 3′ end of the Hepatitis C virus genome using surface plasmon resonance

Abstract: Surface plasmon resonance was used to investigate two previously described interactions analyzed by reverse genetics and complementation mutation experiments, involving 5BSL3.2, a stem-loop located in the NS5B coding region of HCV. 5BSL3.2 was immobilized on a sensor chip by streptavidin-biotin coupling, and its interaction either with the SL2 stem-loop of the 3 ′ end or with an upstream sequence centered on nucleotide 9110 (referred to as Seq9110) was monitored in real-time. In contrast with previous results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 56 publications
5
50
0
Order By: Relevance
“…In agreement with the previous findings, 71, 72 the 5BSL3.2:3′X complex band can be detected only in gels containing Mg 2+ [see Fig. 5].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with the previous findings, 71, 72 the 5BSL3.2:3′X complex band can be detected only in gels containing Mg 2+ [see Fig. 5].…”
Section: Resultssupporting
confidence: 93%
“…6870 Previous gel electrophoresis and surface plasmon resonance (SPR) studies have shown that in vitro transcribed 5BSL3.2 and 3′X can form an RNA:RNA complex and Mg 2+ is required in the gel and running buffer in order to detect the RNA complex band. 71, 72 We apply the PCTBI model developed in the present study to investigate the physical mechanism for the Mg 2+ -dependence of the folding stability and the shift of conformational equilibrium for the 5BSL3.2:3′X kissing complex. Our results indicate that Mg 2+ ions can indeed stabilize the 5BSL3.2:3′X docked state over the undocked state and for 3′X, adding Mg 2+ to the solution shifts the conformational equilibrium toward the kissing conformation.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Kinetic titration assays [24] were first performed with model compound 3 on HCA immobilized on the chip, and gave a K D value of approximately 5 nm (Figure 1). [23] Kinetic titration assays [24] were first performed with model compound 3 on HCA immobilized on the chip, and gave a K D value of approximately 5 nm (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…25,30,32 The three-stem–loop (3SL) model (Figure 1C) is believed to be the dominant conformation because the kissing-loop residues in SL2 (nucleotides 9582–9588) are readily exposed and thus supports the long-range 5BSL3.2:3′X interaction. 1113 The interaction between the SL2 and 5BSL3.2 RNA fragments has been observed by in vitro RNA:RNA binding assays, 23,33 but not by nuclear magnetic resonance (NMR) analysis. 11 Selective 2′-hydroxyl acylation analyzed by primer extension (SHAPE) and chemical probing studies showed that the nucleotide activities of 3′X residues were different in the presence of 5BSL3.2, 19,34 supporting the proposed 5BSL3.2:3′X interaction.…”
mentioning
confidence: 99%